(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The step-up approach to necrotising pancreatitis, introduced by van Santvoort and colleagues in the PANTER trial [1], established the principle that percutaneous drainage and video-assisted retroperitoneal necrosectomy should precede open surgery. However, the critical limitation of conventional step-up protocols is their dependence on clinical parameters that mature only at 48-72 hours, by which time the window for pre-emptive intervention has often closed. In the emergency surgical centres of Uzbekistan, this problem is compounded by the high proportion of late presentations and a local prevalence of severe AP that exceeds global averages [2]. Integrating molecular-genetic risk stratification at admission offers a means to overcome this temporal constraint: patients carrying three or more risk alleles in the VEGFA, MMP9, SPINK1, CAT and CYP2C19 gene panel have a probability of severe/necrotizing AP exceeding 75%, justifying urgent intervention within the first 12-24 hours rather than watchful waiting [3]. The clinical and economic consequences of implementing such a genetically informed algorithm at scale have not previously been reported.